Répétition - Edgar Degas - Finoskov (NC, 2026)
In the Cantini museum in Marseille (Bouches-du-Rhône, Provence, France), temporary exhibition, from May 18 to September 23, 2018, "Realistic and impressionist masterpieces from the en:William BurrellBurrell collection" from the museum of Glasgow.
Droits : Licence indiquee par Wikimedia Commons
Keywords: Degas; Peintur; Peintures; Tableaux; Musée; musée national; Art